Water temperature variability in the Coos Estuary and its potential link to eelgrass loss - Marin Jarrin, Maria Jose; Sutherland, David A.; Helms, Alicia R. (Frontiers in Marine Science, 2022)
Subtidal water temperatures in estuaries influence where organisms can survive and are determined by oceanic, atmospheric and riverine heat fluxes, modulated by the distinct geometry and bathymetry of the system. Here, we use 14 years of data from the Coos Estuary, in southwest Oregon, USA, to explore the impact of anomalously warm oceanic and atmospheric conditions during 2014-2016 on the estuary temperature. The arrival of a marine heatwave in September 2014 increased water temperature in the greater Pacific Northwest region until March 2015, and again from July to August 2015. Additionally, in 2014-2016, the Equatorial Pacific showed increased temperatures due to El Niño events. In the Coos Estuary, this warming was observed at all the water quality stations, producing more than 100 days with temperatures at least 1.5°C warmer than normal, and notably, a higher prevalence during Fall and Winter seasons. Larger temperature variations occurred at shallower stations located further away from the mouth of the estuary, changing the along-estuary temperature gradient and potentially the advection of heat through the estuary. After the onset of these increased temperatures, eelgrass declined sharply, but only in certain stations in the shallow estuary South Slough and has not yet returned to long term average values. As global temperatures continue rising due to climate change, increased numbers of marine heatwaves and El Niño events are expected, leading to higher temperature stress on the marine ecosystem within estuaries.